DESIGN OF MEASURING AND MONITORING DEVICE BASED ON MICROCONTROLLER AND ANDROID - Akhmad Solikin; Winarno Fadjar Bastari; Achmad Aripin (BEST, 2023)
Heart health is an important thing to monitor, because the heart is an important vital organ and is prone to disturbances, especially for the elderly. Such as stroke, arrhythmia and other heart diseases. Usually a heart rate detector is only owned by people who work as health workers and health agencies, and if someone who has heart disease such as stroke and arrhythmia wants to check his heart health, he must come to a doctor or health agency. Therefore, a measuring device and monitoring of heart rate are made on a regular basis. This heart rate measuring and monitoring device is based on a microcontroller and android with a periodic database-based monitoring system. By using the MAX 30100 sensor which has an average error of approximately 3% with a difference value of more than 3 bpm with existing standard measuring instruments.